PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN RUMAH SAKIT UMUM DAERAH AJIBARANG - Uty Kustiana; Suwarno; Herwiek Dyah Lestari (Majalah Imiah Manajemen & Bisnis, 2019)
This research is entitled "The Effect of Work Motivation, Work Discipline and Organizational Commitment on Employee Performance of Ajibarang Regional General Hospital". The purpose of this study was to determine the effect of positive significance of work motivation on employee performance at the Ajibarang Regional General Hospital. to determine the effect of positive significance of work discipline on the performance of employees of the Ajibarang Regional General Hospital and to determine the effect of positive significance of organizational commitment on employee performance at the Ajibarang Regional General Hospital. The analysis uses multiple linear regression. Conclusions for this research: Work motivation has a significant positive effect on the performance of employees of the Ajibarang Regional General Hospital with a 95% confidence level received. This is evidenced by t calculated work motivation greater than t table (4.892> 1.6698), so that the hypothesis which states work motivation has a significant positive effect on the performance of employees of the Ajibarang Regional General Hospital, accepted. Work discipline has a significant positive effect on the performance of employees of the Ajibarang Regional General Hospital with a 95% confidence level received. This is evidenced by the t work discipline count is greater than t table (3.785> 1.6698), so the hypothesis which states that work discipline has a significant positive effect on the employee performance of the Ajibarang Regional General Hospital, is accepted. Organizational commitment has a significant positive effect on the performance of employees of the Ajibarang Regional General Hospital with a 95% confidence level received. This is evidenced by t calculating organizational commitment greater than t table (3.320> 1.6698), so that the hypothesis that states organizational commitment has a significant positive effect on the performance of employees of the Ajibarang Regional General Hospital, accepted.